Menopause transition: A cross-sectional evaluation on muscle size and quality - Smith-Ryan, A. E.; Hirsch, K. R.; Cabre, H. E.; Gould, L. M.; Gordon, A. N.; Ferrando, A. A. (Medicine & Science in Sports & Exercise, 2023)
Introduction The menopause transition yields significant physiological alterations. The purpose was to characterize lean soft tissue (LST), muscle size (muscle cross-sectional area (mCSA)), muscle quality (echo intensity (EI)), and strength across the menopause transition. A secondary aim was to evaluate whole-body protein turnover in a subsample of women.